eHealth key issues in Portuguese public hospitals - Cruz-Correia, R.; Nascimento, J. C.; Sousa, R. D.; O'Neill, H. (2012 25th IEEE International Symposium on Computer-Based Medical Systems (CBMS), 2012)
Hospital managers, health and IT Professionals have their work increasingly supported and dependent on information systems and technologies. To be more effective and efficient in the way health care is delivered, considerable improvements in health information systems and technologies still have to be made at the local and national levels. This is a study that seeks for a deeper understanding of the Portuguese hospitals main stakeholder's concerns regarding their interaction with Information Technology, so opportunities for improvement can be later identified. Seven public hospitals have been selected to participate in this study. In each hospital, managers, IT and health professional were interviewed leading to the discussion of some global and shared perceptions that resulted in a list of eHealth key issues in public Portuguese hospitals.